2014
DOI: 10.1109/jdt.2014.2300488
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Color Impression for Spatially Mixed Colors

Abstract: Display devices adopt multiprimary pixels to represent chromatic images, and the individual primary pixels are discernible dimly within a certain range of spatial frequency. We systematically investigate the color impression of spatially mixed patterns of two colors from a barely discernible distance and show that the color impression differs greatly from their physically averaged colorimetric color. A large degree of luminance-enhanced perception is observed in all mixed color patterns, and significant chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The present study investigated the characteristics and mechanisms of representative color perception for 120 kinds of real-world surfaces, most of which involved highly complex structures and non-uniform material properties. The results showed that observers matched representative colors with higher lightness and saturation than the mean of the image, which is partially consistent with previous findings 24 , 25 , 28 , 31 , 36 , 37 . More importantly, the present study revealed that the perceived representative colors for the original images were not different from those for the PS-synthesized and from those for phase-randomized images except for one.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study investigated the characteristics and mechanisms of representative color perception for 120 kinds of real-world surfaces, most of which involved highly complex structures and non-uniform material properties. The results showed that observers matched representative colors with higher lightness and saturation than the mean of the image, which is partially consistent with previous findings 24 , 25 , 28 , 31 , 36 , 37 . More importantly, the present study revealed that the perceived representative colors for the original images were not different from those for the PS-synthesized and from those for phase-randomized images except for one.…”
Section: Discussionsupporting
confidence: 91%
“…Instead, the results support the idea that the perception of representative colors depends on low-level image measurements, in contrast to the perception of the other material properties. It should be noted that these results are obtained for 120 real-world surfaces with much larger variations and higher ecological validity than those used in most of the previous studies 5,7,8,13,19,30,31,36,37 .…”
Section: Experiments 2: Synthetic Texture Imagesmentioning
confidence: 65%
See 1 more Smart Citation
“…By investigating single color impression of multicolored texture patterns or natural objects, several researchers came to the conclusion that color impression cannot be simply determined by a colorimetric average of elemental colors but is influenced by a mechanism that integrates the color appearance attributes (hue, saturation, and brightness) of elemental colors . Moreover, some authors claim that an overall color impression strongly depends on the most saturated elemental colors, which result in a chromatic enhancement in perceived single color impression . Others share the opinion that an overall color impression can be predicted by averaging color appearance attributes of elemental colors.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Moreover, some authors claim that an overall color impression strongly depends on the most saturated elemental colors, which result in a chromatic enhancement in perceived single color impression. 9,11 Others share the opinion that an overall color impression can be predicted by averaging color appearance attributes of elemental colors. For example, Milojevic et al discovered that the natural object's color category largely depends on the object's mean hue and is not shifted toward the most saturated colors.…”
mentioning
confidence: 99%